2019
DOI: 10.1007/s10120-018-00917-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between UGT1A1 gene polymorphism and safety and efficacy of irinotecan monotherapy as the third-line treatment for advanced gastric cancer

Abstract: Background While uridine diphosphate glucuronosyltransferase (UGT) 1A1 is a key enzyme in the metabolism of irinotecan, relationship between UGT1A1 genotype and safety and efficacy of irinotecan monotherapy in patients with advanced gastric cancer is not clarified. Methods Efficacy and safety in advanced gastric cancer patients, who were tested for UGT1A1*6 and *28 genotype and treated with irinotecan monotherapy as third-line treatment from 2009 to 2014, were evaluated according to the UGT1A1*6 and *28 genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
(25 reference statements)
3
14
0
Order By: Relevance
“…This trend was also shown regardless of treatment line and use of taxanes. Non-hematological toxicity such as diarrhea did not significantly differ according to UGT1A1 status, consistent with the findings of previous studies [13,23,24]. To date, few studies and guidelines have mentioned the impact of However, clinicians should be aware that not only double heterozygous or homozygous UGT1A1, but also SH is a significant risk factor for severe hematological AEs.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This trend was also shown regardless of treatment line and use of taxanes. Non-hematological toxicity such as diarrhea did not significantly differ according to UGT1A1 status, consistent with the findings of previous studies [13,23,24]. To date, few studies and guidelines have mentioned the impact of However, clinicians should be aware that not only double heterozygous or homozygous UGT1A1, but also SH is a significant risk factor for severe hematological AEs.…”
Section: Discussionsupporting
confidence: 88%
“…Nishimura et al [23] reported a higher incidence rate of hematological toxicity in irinotecan monotherapy as third-line treatment for AGC refractory to fluoropyrimidines, platinum, and taxanes. Yamaguchi et al [13] reported a similar rate of toxicity in third-line irinotecan monotherapy between UGT1A1 WT and SH patients. The discrepancy may be explained by the different rates of initial dose reduction of irinotecan.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations